A Comparative Study of Z-Source Inverter Fed Three-Phase IM Drive with CSI and VSI fed IM - Deepak Kumar; Zakir Husain (Institute of Advanced Engineering and Science, 2013)
This paper cite comparative performance characteristics of Z-Source inverter fed IM drives with mostly used VSI & CSI fed IM drives. ZSI has both voltages buck and boost capabilities as they allow inverters to be operated in the shoot through state. It employs an exclusive Z-Source network (LC component) to dc-link the main inverter circuit to the power source (rectifier). By controlling the shoot-through duty cycle, the inverter system using IGBTS reduces the line harmonics, improves power factor, increases reliability and extends output voltage range. It has reduced harmonics, low switching stress power and low common mode noise as compared to VSI. Simulation results are given to compare the behavior of conventional and proposed topology and also demonstrate the new features of the improved topology i.e ZSI fed IM. Simulation results of ZSI fed IM gives different performance characteristics as compared to VSI & CSI fed IM drives such as its stator & rotor current characteristics, speed characteristics , torque characteristics which put a gloss on the VSI fed IM performance.DOI: http://dx.doi.org/10.11591/ijpeds.v3i3.3869